Developing a rapid assessment tool for identifying and safeguarding pollinators: A case study from a global avocado company - Keira Dymond; Juan L. Celis‐Diez; Carl Lymna‐Dennis; Valeska Rojas‐Bravo; Jaime Martínez‐Harms; Simon G. Potts; Michael P. D. Garratt (Conservation Science and Practice)
Abstract Agricultural intensification poses a global threat to many wild species, including insect pollinators. Despite the dependence of many companies on insect‐pollinated crops within their supply chains, only a limited number of them actively implement measures to protect pollinators. This study aims to address this issue by developing a tool that businesses can employ to create effective pollinator conservation strategies. To create this tool, we utilized an existing roadmap as a foundational structure and adapted it into a practical tool through a comprehensive review of the literature and the development of specific methodologies. Subsequently, we applied this tool to a case‐study company to further refine the methods and gather industry feedback. The developed tool identifies seven specific activities that companies can implement to achieve the following objectives: (1) understand the threats to pollinators, (2) recognize the significance of pollinators to their business (3) assess current pollinator actions, and (4) explore additional pollinator protection measures. The results from our case study indicate that increasing knowledge transfer to growers and supporting them to participate in environmental certification schemes could serve as effective strategies. The tool developed in this study aims to assist companies in identifying effective strategies to safeguard pollinators. Its potential implementation across a wide range of companies could greatly benefit growers and contribute to the conservation of various pollinator species.